2011
DOI: 10.1167/iovs.11-7328
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Macular Degeneration and the Other Double Helix The Cogan Lecture

Abstract: The study and therapy of age-related macular degeneration (AMD), a leading cause of blindness worldwide, have taken great strides over the past decade. During the same time, a central role for RNA in many human diseases has been discovered. We have identified anti-angiogenic functions for synthetic double stranded RNAs (dsRNAs) in neovascular AMD and cytotoxic functions for endogenous dsRNAs in atrophic AMD. These findings provide new insights into the pathogenesis and therapy of both forms of AMD. (Invest Oph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
(27 reference statements)
0
22
0
Order By: Relevance
“…Although many, or most, of the 48 correlated genes populating this category (see Supplemental Table 3) have roles in development and growth of other tissue types, all have also been linked to vasculature development. While the functional significance of this is difficult to discern at present, it may be relevant that angiogenesis is a well-established co-factor in tumor growth, and plays a key role in retinal macular degeneration (Ambati, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Although many, or most, of the 48 correlated genes populating this category (see Supplemental Table 3) have roles in development and growth of other tissue types, all have also been linked to vasculature development. While the functional significance of this is difficult to discern at present, it may be relevant that angiogenesis is a well-established co-factor in tumor growth, and plays a key role in retinal macular degeneration (Ambati, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…AMD is the leading cause of irreversible vision loss in modern Western societies among adults over 50 and is projected to impact the lives of nearly 200 million people worldwide by the year 2020 (1)(2)(3)(4). It presents in two distinct forms, based on the types of lesions that occur in the late stages.…”
mentioning
confidence: 99%
“…TLR3 and 7 are reportedly expressed in tissues and cells involved in the pathogenesis of AMD, including the RPE, macrophages, dendritic cells, as well as neural tissue (Ambati et al, 2003;Hageman et al, 2001;Kumar et al, 2004;Lee et al, 2007;Prehaud et al, 2005;Tsutsumi et al, 2003). Although it has been suggested that TLR3 variations may be associated with GA and CNV (Ambati, 2011;Kleinman et al, 2012;Yang et al, 2008) such association and those of TLR4 and 7 with AMD are not supported by Fig. 5.…”
Section: Discussionmentioning
confidence: 92%
“…TLRs have been associated with a number of ocular vascular and inflammatory diseases. TLR3 variations are associated with geographic atrophy (GA) and choroidal neovascularisation (CNV) (Ambati, 2011;Yang et al, 2008). Klettner et al (2013) reported the induction of cell death in RPE cells by TLR3 activation as a possible mechanism of GA.…”
Section: Introductionmentioning
confidence: 99%